Consequences of micronutrient coated urea for maximizing N-uptake - Babar, Saima Kalsoom; Yusop, Mohd Khanif; Gandahi, Rabail (2015)
Nitrogen (N) losses from agricultural fields are commonly observed particularly from urea. To minimize ammonia (NH3) voltalization the micronutrient coated urea is applied to enhance N-efficiency. This study is an application of micronutrient coated urea with zinc (Zn) and copper (Cu) for two soil series of Malaysia. A laboratory experiment was designed according to the force draft technique for trapping the NH3 loss. The results manifested the rate of ammonia voltalization is 16% for uncoated urea and 8% for coated urea with micronutrients during first two weeks of the observation. It was observed that the ammonia loss gradually decreased with the time for both soil series. The mean comparison has shown the positive effect of Zn and Cu coated urea in comparison with the other treatments. The overall results revealed the efficacy of micronutrient coated urea on both soil series to maximize N-uptake and reduce NH3 voltalization.